Protecting Groups for the Synthesis of Ribonucleic Acids - Stefan Pitsch (CHIMIA, 2001)
Methods for the regioselective introduction of alkoxymethyl-groups into the 2?-O-position of 5?-O-dimethoxytritylated, nucleobase-protected ribonucleosides and for the N-alkyloxycarbonylation of adenine and guanine nucleosides were developed. These methods were used for the preparation of RNA-phosphoramidites carrying novel fluoride- and photolabile sugar and nucleobase protecting groups.